An analysis of provincial infant mortality differentials in the Philippines. - Sumagaysay, Marieta Banez, 1961- . (Quezon City Marieta Banez Sumagaysay, 1988)
Using a reduced-form health production function adopted from Schultz (1984), this study examines the socio-economic determinants of provincial infant mortality differentials in the Philippines. The framework is a microeconomic analysis of the demographic behavior of households in choosing and demanding inputs which will minimize infant moratlity, the health outcome. The independent variables are: (a) economic endowments of the individuals/households including human and nonhuman capital: income/wealth, and maternal education; and (b) community-based interventions and environmental constraints: sanitation, social structure/organization, physical infrastructure, and health and social services. These indirectly affect infant mortality through more proximate variables, namely: parental, nutritional, infection, and childcare factors (Chen, 1981).
To determine the significant provincial level factors affecting infant mortality, the ordinary least squares estimation technique is used. Results show that in all the alternative specifications, maternal education at the elementary level, EDW (1-6), and household density, HO/DU, are significantly different from zero at the 95 percent level. EDW (1-6) has a strong negative effect on infant mortality which implies that provinces with more mothers having 1 to 6 years of education as opposed to none experience lower infant mortality. On the other hand, HO/DU shows a positive effect which suggests that congestion and crowding in the house increases the incidence of airborne diseases, therefore, mortality risk.
All the ramaining socio-economic variables exhibit the expected direction of causation with Total IMR, but not to a level of significance. EMPW and RURAL show positive effects while YCAP, WATER, TOILET, ELEC, IRRIG, BEDS, HILAND, and POPDEN show negative effects. Results further show no significant differences between sexes which implies that the infant health production function specified in the model is not adequate to capture inputs determining sex infant mortality differentials.
Keywords: Infant mortality -- Philippines